P083: Why do older adults in assisted living facilities use the emergency department: are all these visits necessary?. (2nd June 2016) - Losier, E.; McCollum, A.; Jarrett, P.; McCloskey, R.; Nicholson, P.; Howlett, M.
Abstract : Introduction: Special Care Home (SCH) residents require supervision for activities of daily living but not regular nursing care. Emergency Department (ED) use by seniors in SCHs is poorly studied. A recent study in Nova Scotia found seniors represented over 20% of ED visits. We studied SCH resident ED visits in a community with a population of 30, 000 aged over 65 years and with 785 SCH beds, to define reasons for ED visits to a tertiary ED, and if these could be avoided.Methods: We performed a retrospective chart review of SCH residents' visits to an ED (SCH-ED) which has 56, 000 total ED (TED) visits over one year. Reasons for visit, admission data, and avoidability were collected. A geriatrician and ED physician independently reviewed visits. Initial disagreement on avoidability (27%) was adjudicated through case discussion.Results: Demographic data revealed 344 ED visits by 111 SCH residents over one year; 37% of visits resulted in admission. 13.9% of residents visited the ED on at least one occasion (average 3.1 visits); mean age 78.4 years; female 66.7%; ambulance arrival 91.0%. The three most common chief complaints were shortness of breath, weakness and abdominal pain . Most SCH-ED visits were Canadian Triage and Acuity Scale (CTAS) Level 3 (63.4%, TED 53.3%). Of CTAS Level 3 visits, 35.3% were admitted (TED 12.9%). SCH-ED visits were avoidable in 40.6% of cases. Gastrointestinal (18%), pain (16.5%), falls, functional decline or injury (14%) and respiratory (12%) were the most common avoidable diagnostic groups, accounting for 57% of total SCH visits.Conclusion: ED visits by SCH residents demonstrated increased acuity and admission rates with a high number of repeat visits. Of all SCH-ED visits, 40% were potentially avoidable. Further study may determine if improved community services reduces ED visits or hospital admission. Gastrointestinal, respiratory, falls and pain diagnoses may be important areas of focus.